Establishment of a tagged variant of Lgr4 receptor suitable for functional and expression studies in the mouse - Kriz, Vitezslav; Krausova, Michaela; Buresova, Petra; Dobes, Jan; Hrckulak, Dusan; Babosova, Olga; Svec, Jiri; Korinek, Vladimir (Transgenic research, 2017)
Leucine-rich repeat-containing G-protein-coupled receptor 4 (LGR4) is produced in a broad spectrum of mouse embryonic and adult tissues and its deficiency results in embryonal or perinatal lethality. The LGR4 function was mainly related to its potentiation of canonical Wnt signaling; however, several recent studies associate LGR4 with additional signaling pathways. To obtain a suitable tool for studying the signaling properties of Lgr4, we generated a tagged variant of the Lgr4 receptor using gene targeting in the mouse oocyte. The modified Lgr4 allele expresses the Lgr4 protein fused with a triple hemagglutinin (3HA) tag located at the extracellular part of the protein. The allele is fully functional, enabling tracking of Lgr4 expression in the mouse tissues. We also show that via surface labeling, the 3HA tag allows direct isolation and analysis of living Lgr4-positive cells obtained from the small intestinal crypts. Finally, the HA tag-specific antibody can be employed to characterize the biochemical features of Lgr4 and to identify possible biding partners of the protein in cells derived from various mouse tissues.
Keywords: Protein Binding; Receptors, G-Protein-Coupled; tkáňová distribuce; TALENs; R-spondin; Wnt Signaling Pathway; Wnt signaling; oocyty; Hemagglutinin tag; Tissue Distribution; Pregnancy; těhotenství; genový targeting; Hemagglutinins; Gene Targeting; Knock-in; vazba proteinů; Animals; lidé; ženské pohlaví; hemaglutininy; Humans; zvířata; receptory spřažené s G-proteiny; myši; Alleles; Mice; signální dráha Wnt; Female; alely; Genome editing; Oocytes